Online Learning Based on Realistic Mathematic Education (RME) Assisted Animation Media in Improving Student Learning Outcomes - Titin Handayani Amir; Agustan Syamsuddin; Sulfasyah Sulfansyah (Universitas Pendidikan Ganesha, 2021)
There are still many teachers who have difficulty determining appropriate learning methods and learning media for mathematics lessons. This has an impact on student learning outcomes are low. This study aims to analyze the effect of the Realistic Mathematical Education (RME) approach assisted by animation media on students' mathematics learning outcomes. This research is a quantitative research with a quasi-experimental research design with a non-equivalent control group design research design. This study involved 30 students as the research sample with a simple random sampling technique (Simple Random Sampling). This study uses data collection techniques, namely observation and written tests by giving five essay questions with different weights for each question. The data obtained were analyzed using the SPSS v.22 application by looking for the results of the normality test, homogeneity test, N-Gain test and finally the t-test (Independent Sample Test) to test the hypothesis. The results showed that there was a difference between the students' average scores by applying the Realistic Mathematical Education (RME) approach with the aid of animation media, obtaining an average score of 74.60 in the medium category. Based on the results of data analysis, there is a significant effect on mathematics learning outcomes which can be proven from the significance value at the output of the Independent Sample Test, namely 0.000 < 0.05, which means that H0 is rejected and Ha is accepted. It can be concluded that the Realistic Mathematical Education (RME) approach assisted by animation media can improve mathematics learning outcomes.